Докази та доказування у цивільному процесі на українських землях Російської Імперії у першій половині ХІХ ст. (до реформи 1864 р.) - Брусакова, О. В.; Brusakova, O. V.; Оксана Брусакова (Науковий вісник Львівського державного університету внутрішніх справ. Серія юридична. – 2018. – Вип. 3. – С. 3-11, 2018)
Досліджено питання про докази та доказування у цивільному процесі першої половини ХІХ ст., до судової реформи 1864 р. Розкрито, що визнавалося доказами у позовних справах у цивільному процесі відповідно до чинного тоді законодавства, як відбувалося доказування під час судового розгляду, яке значення мало власне зізнання, що вважалося письмовим доказом. Проаналізовано відповідні статті Зводу законів Російської імперії (Закони про судочинство і стягнення цивільні).

According to the law in force during this period, the evidence in the lawsuits was recognized as proper confession; written evidence (acts); personal review; testimony of knowledgeable people (in fact, experts); testimonies of witnesses; 6. general search; oath. Those who could not be a witness are the young (up to 15 years old); the mad (mentally ill), the deaf, murderers, robbers, persons who have never been in the holy communion, foreigners, whose behavior was unknown. All evidence was divided into two parts: 1. perfect, which did not provide any options for the recognition of the defendant innocent; 2. imperfect when such a possibility was provided and the defendant could be found innocent. To perfect evidence, the law included: personal accusation of the accused, written evidence acknowledged by him, the conclusion of medical experts, testimony of two witnesses who were not identical and not refuted by the defendants. The imperfect evidence was: extrajudicial confession of the accused, confirmed by witnesses; the ban of third parties; general search; testimony of one witness. The assessment of the importance of testimony of the parties and their witnesses in the court in the then law clearly pointed to the application of this class principle. At the testimony of witnesses, in case of their contradiction, the preference was given to a man over a woman who was notable before the infallible, educated over those who are not, spiritual before the secular. In addition, National and religious inequality of witnesses should be considered. If the judge believed that the number of documents submitted to the case was sufficient, then, summarizing the materials of the civil case, court chancellery used them to prepare the extract of the case. Proofing took place in a court where judges were guided by the above mentioned extract. The trial was not considered publicly and the trial phase of the process in its absolute majority ended with the fact that the judges approved the conclusions of the extract.

Исследован вопрос о доказательствах и доказывания в гражданском процессе первой половины XIX в., до судебной реформы 1864 г. Раскрыто, что признавалось доказательствами в исковых делах в гражданском процессе в соответствии с действующим тогда законодательством, как происходило доказывания в ходе судебного разбирательства, какое значение имело собственное признание, что считалось письменным доказательством. Проанализированы соответствующие статьи Свода законов Российской империи (Законы о судопроизводстве и взыскания гражданские).
Keywords: Цивільне право. Civil Law. Гражданское право; Наукові публікації. Scientific publications. Научные публикации; Цивільно-процесуальне право. Civil and Procedure Law. Гражданское процессуальное право; Історія. History. История; Україна. Ukraine. Украина; українські землі; украинские земли; Ukrainian lands; Російська імперія; Российская империя; Russian Empire; докази; evidence; доказательства; доказування; доказывание; proving